2015
DOI: 10.1148/radiol.15142005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of an Advanced Modeled Iterative Reconstruction Algorithm for Low-Contrast Detectability with a Third-Generation Dual-Source Multidetector CT Scanner: Potential for Radiation Dose Reduction in a Multireader Study

Abstract: Low-contrast detectability performance increased with increasing object size, object contrast, dose index, section thickness, and ADMIRE strength. Compared with FBP, ADMIRE allows a substantial radiation dose reduction while preserving low-contrast detectability. Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 19 publications
6
134
3
Order By: Relevance
“…The use of iterative reconstruction (ADMIRE) at a strength of 2 decreased noise by about 20% throughout all images and therefore further improved the CNR of the VMIs. This is consistent with other published data which demonstrated that low‐contrast detectability is increased by decreasing noise of DECT images using iterative reconstruction 6, 13, 19. These data suggests that the best tumor visibility can be achieved by contouring on VMIs at 40 keV with ADMIRE, although this may still depend on physician preference, window and leveling.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The use of iterative reconstruction (ADMIRE) at a strength of 2 decreased noise by about 20% throughout all images and therefore further improved the CNR of the VMIs. This is consistent with other published data which demonstrated that low‐contrast detectability is increased by decreasing noise of DECT images using iterative reconstruction 6, 13, 19. These data suggests that the best tumor visibility can be achieved by contouring on VMIs at 40 keV with ADMIRE, although this may still depend on physician preference, window and leveling.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggests that the best tumor visibility can be achieved by contouring on VMIs at 40 keV with ADMIRE, although this may still depend on physician preference, window and leveling. While increasing the strength of iterative reconstruction may further improve CNR,19 further investigation into the effects of ADMIRE on edge detection and therefore tumor delineation is needed. In addition, further investigation is needed to determine the impact of increased CNR in VMIs on the accuracy of tumor delineation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] Several previous studies have demonstrated a good correlation between the performance of human observer and model observer. [17][18][19][21][22][23] Most of these studies were performed using phantoms with uniform background due to simplicity and availability of these phantoms. However, to assess image quality and radiation dose reduction in clinical CT imaging, physical phantoms having realistic background textures and lesions are highly desirable as the performance of reconstruction algorithms may be affected by anatomic background (i.e., structured noise).…”
Section: Introductionmentioning
confidence: 99%
“…47 One study assessed the effect of ADMIRE on low-contrast detectability in a contrast-detail phantom, when compared to the FBP algorithm. 48 The results demonstrated an average increase of 5.2% (p-value<0.001) in detection accuracy with the use of ADMIRE, and low contrast detectability increased with increasing object contrast, size, dose index and strength of AD-MIRE. The use of the ADMIRE algorithm allowed a significant reduction in dose that ranged from 56% to 60% and 4% to 80% in 2 reading sessions, while preserving low-contrast detectability.…”
Section: Performance Of Safire and Admire Algorithmsmentioning
confidence: 86%